PENGARUH INOVASI PRODUK KUALITAS LAYANAN TERHADAP LOYALITAS NASABAH BNI CABANG UGM YOGYAKARTA DENGAN KEPUASAN NASABAH SEBAGAI VARIABEL MEDIASI - Sari, Cindy Kartika; Chasanah, Uswatun (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2023)
The approach taken by banks is to redesign the approach in order to be able to win the competition by adjusting existing regulations so that customers or prospective customers are comfortable doing financial transactions without the need for much direct interaction. The quality of service provided by the company has a direct impact on consumers. If the service received exceeds customer expectations, then service quality is perceived as an ideal quality. Thus, whether or not the quality of service depends on the ability of service providers to meet customer expectations consistently and continuously.